Comparative anatomy of the vegetative systems of eight Cyrtopodium R. Br. species (Orchidaceae, Epidendroideae) occurring in Central Brazilian savannas - dos Santos, Igor Soares [UNESP]; Melo-de-Pinna, Gladys Flávia de Albuquerque; da Silva, Marcos José (Elsevier, 2023)
Cyrtopodium comprises 50 species, 37 of which are found in Brazil, with 19 being endemic. Some of the Brazilian species are morphologically similar, with similar life forms, and are often confused in herbarium collections. We tested whether the anatomical characters of the vegetative systems of eight species of the genus occurring in savanna areas of Central Brazil could be used to differentiate them, or if those differences reflect environmental conditions. We found that: i) the studied species can be differentiated by leaf characters (e.g., the types and locations of their epicuticular waxes and cuticle ornamentations, the presence or absence of prismatic crystals and trichomes, midrib contour, composition and orientation of the leaf margin, numbers and arrangements of the vascular bundles), by pseudobulb characteristics (e.g., the shapes of the subepidermal cells), and by radicular characteristics (e.g., numbers of cortex and velamen layers, the presence or absence of trichomes, phi thickening, spiral idioblasts, the numbers of protoxylem poles); and that, ii) the thick cuticle of the pseudobulb, the density of waxes, and the presence of supra- and substomatal chambers in the leaves, as well as tilosomes and the numbers of layers of velamen in the roots, may reflect adaptations to environmental conditions and life forms. Additionally, we report here for the first time for the genus, the presence of crystals in epidermal cells, striae and epicuticular waxes, root trichomes, phi thickening, and spiral idioblasts, and describe the ascending and tangled trash-basket roots of C. saintlegerianum in an ecological-functional context associated with epiphytism.
Keywords: Cerrado; Diversity; Ecology; Micromorphology; Orchids; Taxonomy